Barriers to Enrollment in Health Coverage in Colorado - Martin, Laurie T. (RAND Corporation, 2014)
Although, under the Affordable Care Act, Colorado has expanded Medicaid and also now operates its own health insurance exchange for individuals, there continues to be a diverse mix of individuals in Colorado who remain eligible for but not enrolled in either private insurance or Medicaid. This report explores the reasons for this and makes recommendations on how Colorado can strengthen its future outreach and enrollment efforts.